Colin Gunton's Trinitarian theology of culture: towards a living sacrifice of praise - Picard, Andrew (T&T Clark studies in English theology, 2024)
"This book critically engages Colin Gunton's trinitarian theology of culture in the context of modern debates in trinitarian theology, and argues, against critics, that Gunton's trinitarian theology remains defensible and fruitful for contemporary conversations in theology and culture"--